3D Laparoscopy-Assisted Operation to Adult Intussusceptions During Perioperative Period of Liver Transplantation: Case Report and Literature Review - Gao, Qing; Yuan, Shuo; Li, Yang; Chen, Chao; Liu, Xiaosun; Yu, Jiren (Frontiers in Surgery, 2021)
Adult intussusception during perioperative period is defined as an extremely rare condition, especially when it emerges within short intervals of laparotomy, which may be explained as unphysiological peristaltic function of bowel without any lead points. Accurate diagnosis and therapeutic schedule predict a satisfactory outcome. Here we introduce the case that a 32-year-old man had symptoms of abdominal pain, no gas emission and defecation shortly after liver transplantation. Intussusception was definitely diagnosed by abdominal computed tomograph(CT), and then reduction was operated successfully by three-dimensional(3D) laparoscopy-assisted operation. No any complaints and secondary lesions were detected during the process of postoperative rehabilitation in hospital and over a follow-up period of six months. And relevant literatures has been summarized subsequently. A promising minimally invasive surgery along with minimal secondary trauma was presented by laparoscopy in this rare case, providing the potential remedy for perioperative intussusception in adult.